Application of response surface methodology in process parameters optimization for phenol mineralization using Fenton's peroxidation - Hasan, D.B.; Abdul Raman, Abdul Aziz; Daud, Wan Mohd Ashri Wan (Academic Journals, 2011)
Adverse effect of the highly biorecalcitrant compound phenol to the environment is well established and its concentrations in industrial effluents vary greatly from 2.8 to 6,800 mg/l depending on the source. Fenton process effectively mineralises to CO 2 and H 2O but reported works consumed more reagents and require longer reaction times. Due to the strong interaction between the several predictor variables in the Fenton oxidation, response surface methodology was used to optimise the mineralization treatment. Efficient, faster and economical operating conditions for phenol removal were explored by investigating four parameters namely the concentration ratio of hydrogen peroxide to phenol-((H 2O 2):(Phenol)), mass ratio of hydrogen peroxide to ferrous ions-((H 2O 2):(Fe 2+)), initial phenol concentration - (Phenol o) and reaction time - (t r). The optimal TOC % reduction obtained were 35 and 88% for initial phenol concentrations of 100 and 5 mg/l, respectively. Reaction conditions corresponding to this phenol mineralization a reaction time of 20 min at ratios of 6 and 15 for H 2O 2:Phenol and H 2O 2:Fe 2+, respectively. For mineralisation at 52.5 mg/l phenol concentration, the optimal conditions were 20 min, ratios 10 and 15 for the reaction time, H 2O 2:Phenol and H 2O 2:Fe 2+, respectively. The soluble iron content of the analysed supernatant was found to be below the 15 mg/l (the maximum limit allowable for total iron discharges required by common regulative subscribed). This indicated that, the Fenton reagents were utilised during the peroxidation reaction evident from the almost near consumption of all Fe 2+ introduced in about 85% of the samples, thus, negating the need for immobilising the Fe 2+ catalyst or its removal by post treatment. The work proves that the optimized Fenton process can be potentially used for treatment of any phenol containing wastewater. Â© 2011 Academic Journals.